DAMPAK PENINGKATAN TARIF PPN TERHADAP OMZET PENJUALAN PADA PT XYZ - Nikmatul Ula Wila; Nur Aini Anisa2 (DFAME Digital Financial Accounting Management Economics Journal, 2025)
Ula Wila, Nikmatul, 2062401774, "The Impact of Increased VAT Rates on Sales Revenue at PT XYZ," Youth College of Economics, Advisor Nur Aini Anisa, M.Pd. The purpose of this research is to determine the impact of the increase in VAT rates on the sales revenue at PT XYZ. In our surroundings, transactions often occur with the imposition of taxes that are very relevant to Indonesian citizens, and these taxes are objective and not subjective in nature; the tax in question is Value Added Tax (VAT). This research is of a qualitative nature. Data collection techniques used include observation, interviews, and documentation. This research utilizes both primary and secondary data. The results of this research indicate that the increase in the VAT rate from the initial 10% to 11%, which took effect on April 1, 2022, resulted in a decrease in sales revenue at PT XYZ, primarily due to an increase in selling prices.